Bioinformatic characterization of STING expression in hematological malignancies reveals association with prognosis and anti-tumor immunity - Xiang-mei Wen; Xiang-mei Wen; Xiang-mei Wen; Zi-jun Xu; Zi-jun Xu; Zi-jun Xu; Ji-chun Ma; Ji-chun Ma; Ji-chun Ma; Min-jie Zhang; Min-jie Zhang; Min-jie Zhang; et al. (Frontiers in Immunology)
IntroductionStimulator of interferon response cGAMP interactor (STING) is essential for both innate and adaptive immunity. However, a comprehensive molecular characterization of STING expression across hematological malignancies is lacking.MethodsIn this study, the pan-blood-cancer landscape related to STING expression was identified using the GTEx, CCLE, Hemap, and TCGA databases, and the potential value for predicting prognosis was investigated. The relationship between STING expression and immune cell enrichment was assessed in the Hemap database. Moreover, the value of STING in predicting the efficacy of immunotherapy was validated using tumor immune dysfunction and exclusion (TIDE) biomarkers and real-world immunotherapy datasets.Results and DiscussionSTING was found to be relatively highly expressed in acute myeloid leukemia (AML) and chronic myeloid leukemia, with higher STING expression correlated with poorer prognosis in AML. STING expression was positively correlated with immune-related pathways such as IFN-gamma response, IFN-alpha response, and inflammatory response. Cytolytic score and STING expression were positively correlated in some hematological tumors, especially chronic lymphocytic leukemia and mantle cell lymphoma. Interestingly, STING expression was negatively correlated with TIDE biomarkers in AML, suggesting that AML patients with a high STING expression level may benefit from immunologic treatment. Our findings contribute a molecular characterization of STING across hematological malignancies, facilitating the development of individualized prognosis and treatment strategies.